Formation of a zirconium oxide crystal nucleus in the initial nucleation stage in aluminosilicate glass investigated by X-ray multiscale analysis - Yohei Onodera; Yasuyuki Takimoto; Hiroyuki Hijiya; Qing Li; Hiroo Tajiri; Toshiaki Ina; Shinji Kohara (NPG Asia Materials)
Abstract Understanding the nucleation mechanism in glass is crucial for the development of new glass-ceramic materials. Herein, we report the structure of a commercially important glass-ceramic ZrO2-doped lithium aluminosilicate system during its initial nucleation stage. We conducted an X-ray multiscale analysis, and this analysis was used to observe the structure from the atomic to the nanometer scale by using diffraction, small-angle scattering, absorption, and anomalous scattering techniques. The inherent phase separation between the Zr-rich and Zr-poor regions in the pristine glass was enhanced by thermal treatment without changing the spatial geometry at the nanoscale. Element-specific pair distribution function analysis using anomalous X-ray scattering data showed the formation of a liquid ZrO2-like local structural motif and edge sharing between the ZrO x polyhedra and (Si/Al)O4 tetrahedra during the initial nucleation stage. Furthermore, the local structure of the Zr4+ ions resembled a cubic or tetragonal ZrO2 crystalline phase and formed after 2 h of annealing the pristine glass. Therefore, the Zr-centric periodic structure formed in the early stage of nucleation was potentially the initial crystal nucleus for the Zr-doped lithium aluminosilicate glass-ceramic.